Greenhouse gas emissions in the construction industry: An analysis and evaluation of a concrete supply chain - ARIOĞLU, MAHMURE ÖVÜL (ELSEVIER SCI LTD, 2017)
Significant anthropocentric environmental impact derives from civil construction. In developing countries, such as China, Turkey, and Brazil, this sector plays a relatively larger economic role. Adopting sustainable concrete production and usage strategies not only reduces greenhouse gas (GHG) emissions but also decreases consumption of energy and water, two critical commodities likely to be in short supply in developing economies. Moreover, in developing countries, there is uneven and inadequate access to social and economic benefits (e.g., housing, roads, energy, etc.) for a substantial segment of the society. These emerging economy nations will have to engage in large scale civil construction and energy production projects to improve living conditions. As a result, transitioning to a low carbon economy becomes even more critical and at the same time more burdensome for developing countries. Due to the importance of the civil construction industry to Turkey and the industry's adverse impact on GHG emissions and resulting climate change, this study investigates measurement and management of the total GHG emissions for a major tunnel project by a Turkish construction company. As a case study, emission values are calculated for the raw materials constituting tunnel construction rings, which are the major structural component of the tunnel. The GHG emissions-measured in equivalent carbon dioxide, (CO(2)e) -used in this study are the sum of the emissions during the production of the raw materials and emissions during their transportation from the suppliers to the company. The results are also useful across countries who utilize similar concrete specifications as prescribed by regulators and industry associations. A broader sustainability, including socio-economic concerns, is included as complementary discussion to the emissions/environmental calculations. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: Concrete sustainability; Greenhouse gas emissions; Low carbon economy; Supply chain management; LIFE-CYCLE ASSESSMENT; CEMENT PRODUCTION; EMBODIED CARBON; CO2 EMISSIONS; SUSTAINABILITY; PERFORMANCE; STRATEGIES; MANAGEMENT; SECTOR